2020
DOI: 10.3892/ol.2020.11254
|View full text |Cite
|
Sign up to set email alerts
|

High expression of citron kinase predicts poor prognosis of prostate cancer

Abstract: Citron kinase (CIT) is a Rho-effector protein kinase that is associated with several types of cancer. However, the role of CIT in prostate cancer (PCa) is unclear. The current study utilized microarray data obtained from The Cancer Genome Atlas, which was analyzed via Biometric Research Program array tools. Additionally, reverse transcription-quantitative (RT-q)PCR was performed to compare the mRNA expression of CIT in PCa tissue and in benign prostatic hyperplasia. The protein expression of CIT was detected i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 38 publications
(39 reference statements)
1
9
1
Order By: Relevance
“…Prognostic significance of PRC1, KIF14 and CIT has been so far reported in lung, ovarian, breast, cervical, gastric, hepatocellular, bladder and prostate cancers ( 21 25 , 39 45 ), however, the present study demonstrated no prognostic significance of PRC1, KIF14 and CIT for CRC and PDAC.…”
Section: Discussioncontrasting
confidence: 83%
See 4 more Smart Citations
“…Prognostic significance of PRC1, KIF14 and CIT has been so far reported in lung, ovarian, breast, cervical, gastric, hepatocellular, bladder and prostate cancers ( 21 25 , 39 45 ), however, the present study demonstrated no prognostic significance of PRC1, KIF14 and CIT for CRC and PDAC.…”
Section: Discussioncontrasting
confidence: 83%
“…PRC1, KIF14 and CIT transcript expression is dysregulated, mainly upregulated, in several malignancies, e.g., breast, hepatocellular, bladder, prostate and ovarian cancers ( 21 25 ) and therefore, the relevance of these cytokinesis regulators for tumor initiation and progression is being intensively studied currently ( 36 38 ). Transcript levels of all 3 genes strongly correlated together in the present study further demonstrating their importance for cancer progression and potential as potential therapeutic targets.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations